Konsep Muakhah Dalam Pembentukan Karakter Dan Implementasinya Dalam Pendidikan - R Rofiani (UPT Publikasi Ilmiah, 2025)
The concept of muakhah, or fraternal bonding, is a core value in Islamic teachings that emphasizes brotherhood based on faith, responsibility, and social compassion. As an ethical and spiritual principle, muakhah holds significant potential in shaping students’ character to become morally upright, empathetic, and cooperative individuals. In the educational context, muakhah values can serve as a foundation for fostering a spirit of togetherness, solidarity, and collective responsibility. This approach aligns with modern learning paradigms that emphasize collaboration and active participation. The implementation of muakhah in classroom instruction can be realized through cooperative and collaborative strategies, encouraging students to support one another in completing group tasks and to build harmonious relationships as fellow believers. Thus, muakhah is not merely a normative ideal but can be practically applied in character education within the school environment.